Oxford Classics : Teaching and Learning 1800-2000. - Stray, Christopher (Bloomsbury Publishing, 2013)
Oxford, the home of lost causes, the epitome of the world of medieval and renaissance learning in Britain, has always fascinated at a variety of levels: social, institutional, cultural. Its rival, Cambridge, was long dominated by mathematics, while Oxford's leading study was Classics. In this pioneering book, 16 leading authorities explore a variety of aspects of Oxford Classics in the last two hundred years: curriculum, teaching and learning, scholarly style, publishing, gender and social exclusion and the impact of German scholarship. Greats (Literae Humaniores) is the most celebrated clas.